Efeitos de um programa de intervenção domiciliar na satisfação, qualidade de vida e ocupações de cuidadores de adolescentes com paralisia cerebral: estudo de dois casos - Costa, Jacqueline Denubila (Universidade Federal de São Carlos, 2018)
Introduction: Adolescents with cerebral palsy may present, according to the severity of the case, a high level of dependence on their relatives. This factor can have an impact on the health and quality of life of these caregivers. Therefore, it is necessary to reduce the impact of disability on the caregivers and, in this sense, the intervention model focused on the family seeks to offer support, information and respect the needs and desires of families, incorporating such demands in the intervention program. Objectives: to test the effects of a home intervention program for adolescents with cerebral palsy on the quality of life of caregivers. Methodology: This is a two-case study, mixed, almost experimental, comparative, prospective and with pre and post-test. The inclusion criteria used were: caregivers who accompany adolescents with clinical diagnosis of cerebral palsy who are aged between 10 and 19 years, for at least one year and who do not receive any kind of remuneration for care; caregivers of adolescents with cerebral palsy who use wheelchairs in a home environment for at least one year. Two informal caregivers participated, one being 48 years old and the second with 77, both with exclusive dedication to care tasks, as well as the respective adolescents with cerebral palsy (14 and 19 years old). Outcome instruments and equipment used were: Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST 2.0), Canadian Measurement of Occupational Performance (COPM), World Health Organization Quality of Life (abbreviated version WOQHOL-Bref) and use of time, semi-structured interview script and seat simulator and wheelchair backrest. The study was developed in four phases: pre-test, intervention, post-test and follow-up. Data were analyzed from simple descriptive statistical analysis. Results: caregivers raised occupational performance problems related to occupational areas of self care, sleep, leisure and work. After the intervention program, there was an increase in the performance scores for these occupations - mean scores went from 4 to 5.3 for caregiver A and from 6 to 6.3 for caregiver B, maintenance of satisfaction for the occupations raised by the caregiver A (average of 5.3) and increased satisfaction for the occupations indicated by caregiver B (mean went from 4.3 to 4.6). Likewise, there was an improvement in satisfaction with Assistive Technology (AT) and services, with an absolute score increase from 29 to 31 points (caregiver A) and from 12 to 18 points (caregiver B). In addition, in the post-test phase the WHOQOL-BREF scores increased from 92 to 100 for caregiver A and 74 for 77 for caregiver B. However, during the follow-up phase, it was possible to observe a decrease in these scores - returning to 92 for caregiver A and 62 for caregiver B. Caregivers perceive AT as a facilitator for the functionality of adolescents and for their own quality of life. However, they reported barriers related to the size of the resource and the use of adaptations to improve posture. Conclusion: intervention programs that use the assumptions of the family-focused model have demonstrated the potential to impact the quality of life of caregivers, the quality of care tasks exercised and the satisfaction with the use of AT.
Keywords: Paralisia cerebral; Cuidadores; Terapia ocupacional; Qualidade de vida; Família; Uso do tempo; Ocupação; Cerebral palsy; Caregivers; Occupational therapy; Quality of life; Family; Use of time; Occupation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL